Early liver steatosis in children with pediatric Huntington disease and highly expanded CAG mutations. (October 2022) - Squitieri, Ferdinando; Monti, Lidia; Graziola, Federica; Colafati, Giovanna Stefania; Sabatini, Umberto
Highlights: Pediatric Huntington disease (PHD) with Highly Expanded (HE) CAG mutations affects brain and peripheral organs. The liver is one affected peripheral organ showing steatosis in HE-PHD. Higher the mutation size in HE-PHD, earlier the liver steatosis in childhood HD life.